2011
DOI: 10.1002/ange.201101320
|View full text |Cite
|
Sign up to set email alerts
|

A Dimer of Silaisonitrile with Two‐Coordinate Silicon Atoms

Abstract: Dedicated to Professor Raymundo Cea-Olivares on the occasion of his 60th birthday Carbenes and silylenes are among the most important reactive intermediates of carbon [1] and silicon. [2,3] These species play key roles in numerous thermal and photochemical reactions and are extremely important in synthetic chemistry. [1][2][3] The first N-heterocyclic carbene (NHC) that is stable at room temperature was isolated by Arduengo et al. in 1991. [4] The silicon analogue of NHC was reported three years later by We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0
10

Year Published

2011
2011
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 83 publications
0
23
0
10
Order By: Relevance
“…[19] Wir weisen darauf hin, dass die Si-Atome im viergliedrigen Ring Si 2 (NAr) 2 an N-Atomen gebunden sind, die über freie p-Elektronenpaare verfügen und daher elektronische Ladung in die formal leeren p(p)-AOs des Si donieren kçnnen. 2 1(r) der Elektronendichte des Ge 2 Ga 2 -Rings von 1M.…”
unclassified
See 1 more Smart Citation
“…[19] Wir weisen darauf hin, dass die Si-Atome im viergliedrigen Ring Si 2 (NAr) 2 an N-Atomen gebunden sind, die über freie p-Elektronenpaare verfügen und daher elektronische Ladung in die formal leeren p(p)-AOs des Si donieren kçnnen. 2 1(r) der Elektronendichte des Ge 2 Ga 2 -Rings von 1M.…”
unclassified
“…[19] Der Ge 2 Ga 2 -Ring in 1M hat nur ein besetztes s-"lone-pair"-Orbital an den Germaniumatomen, nämlich das HOMOÀ2, während im Si 2 (NAr) 2 zwei besetzte s-"lone-pair"-Orbitale am Si vorliegen. [19] Der Ge 2 Ga 2 -Ring in 1M hat nur ein besetztes s-"lone-pair"-Orbital an den Germaniumatomen, nämlich das HOMOÀ2, während im Si 2 (NAr) 2 zwei besetzte s-"lone-pair"-Orbitale am Si vorliegen.…”
unclassified
“…were determined by X-ray crystallography. Calculated Laplacian distributions support the presence of a lone pair of electrons at each Si center, and accordingly, Staudinger type reactivity between 69 and Me 3 SiN 3 was noted to form the oxidized silaimine Me 3 SiN¼Si(μ-NAr 0 ) 2 Si¼NSiMe 3 (70) [103]. Compound 74 was structurally authenticated by X-ray crystallography, and this study revealed the presence of a short P¼Si multiple bond [2.0718(6) Å ] and second-order perturbation theory identified a significant N-Si negative hyperconjugative interaction between the lone pair on N and the low-lying Si-P π* orbital in 74 [105].…”
Section: Multiply Bonded Silenes and Silynesmentioning
confidence: 75%
“…Moreover, substantial pyramidalization of the Si center adjacent to the carbene-bound Si was noted due to the acquisition of non-bonding (lone pair) character upon coordination of the NHC [95]. In a conceptually related fashion, the Si(IV)imido adduct IPr•SiCl 2 ¼NAr 0 (35) [102] was reduced with KC 8 to give the silaisonitrile dimer (:SiNAr 0 ) 2 (69) as a yellow crystalline solid in a 21% yield (13) [103]. The two terphenyl ligands in 69 form a steric pocket which surrounds the Si 2 N 2 core and intraring Si-N single bonds of 1.755(1) Å avg.…”
Section: Multiply Bonded Silenes and Silynesmentioning
confidence: 99%
“…[6] Die Reaktion des Aryl(tribrom)silans (EMind)SiBr 3 mit drei ¾quivalenten Lithiumnaphthalenid führte zum luft-und feuchtigkeitsempfindlichen, orangefarbenen Tetrasilacyclobutadien Si 4 Ar 4 (1; Schema 1). Dieses zersetzt sich bei Raumtemperatur langsam, in Lçsung und auch im festen Zustand, konnte aber trotzdem durch Rçntgenstrukturana-lyse sowie durch NMR-und UV/Vis-Spektroskopie charakterisiert werden.…”
unclassified